PENGEMBANGAN BUDAYA SEKOLAH UNTUK PENINGKATAN KOMPETENSI PROFESIONAL GURU PADA MTSN 1 TAKENGON - Nazir Usman, Yusrizal, Murniati. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: Organizational culture is a key variable that could encourage the professional development of teachers, which in turn can improve school performance, success or failure of a teacher in the teaching and learning activities required good organizational culture to improve the quality of education. This study aimed to obtain data on organizational culture applied in schools so as to improve the professional competence of teachers. To achieve this study, researchers used a qualitative approach with descriptive methods. Data collection techniques of observation, interviews, and study dokumentsi data analysis procedures are data reduction, data display, and verification, research subjects were principals, vice-principals, and teachers. The results showed that: (1) The development of a culture of discipline in obeying the school rules by principals can improve the professional teachers in improving the quality of school education, (2) development of a culture of responsibility by the principal is always met by the head of the school so that all teachers not play in carrying out its activities as an educator. (3) The development of the culture of shame by principals also continue to be the principal so that the teachers can not play games in the process of teaching and learningKeywords : Cultural School / Organization and Professional Teacher Abstrak: Budaya organisasi merupakan variabel kunci yang bisa mendorong pengembangan profesionalisme guru yang pada akhirnya dapat meningkatkan kinerja sekolah, berhasil atau tidaknya seorang guru dalam kegiatan belajar mengajar dibutuhkan budaya organisasi yang baik untuk meningkatkan mutu pendidikan. Penelitian ini bertujuan untuk mendapatkan data tentang budaya organisasi yang diterapkan disekolah sehingga dapat meningkatkan kompetensi profesional guru. Untuk mencapai penelitian ini peneliti menggunakan pendekatan kualitatif dengan metode deskriptif. Tekhnik pengumpulan data observasi, wawancara, dan study dokumentsi prosedur analisis data adalah reduksi data, display data, dan verifikasi, subjek penelitian adalah kepala sekolah, wakil kepala sekolah, dan guru. Hasil penelitian menunjukkan bahwa : (1) Pengembangan budaya disiplin dalam menaati peraturan sekolah oleh kepala sekolah dapat meningkatkan professional guru dalam meningkatkan mutu pendidikan sekolah, (2) Pengembangan budaya tanggung jawab oleh kepala sekolah selalu dipenuhi oleh kepala sekolah sehingga semua guru tidak bermain-main dalam menjalankan aktivitasnya sebagai pendidik. (3) Pengembangan budaya malu oleh kepala sekolah juga terus dilakukan kepala sekolah sehingga guru-guru tidak bisa bermain main dalam proses belajar pembelajaran.Kata kunci : Budaya Sekolah/Organisasi dan Professional Guru